TOURISM VERSUS MINING: CONTESTED SPACE IN TANJUNG PUTAT BEACH AND LEPAR BEACH, BELINYU DISTRICT, BANGKA REGENCY - Berlian Zarina; Ibrahim Ibrahim; Rini Arcdha Saputri; Rendy Rendy (Faculty of Social and Political Sciences University of Bangka Belitung, 2021)
Tourism is one of the sustainable income sectors that is predicted as a post-mining sector. Thus, the area of tourism activities, especially beaches are minimized to be damaged, including juxtaposing it with mining. The research aims to elaborate on spatial contestation that occurred at Tanjung Putat Beach and Lepar Beach, Belinyu District, Bangka Regency. The theoretical basis used in this research is using the concept of spatial production from Henri Lefebvre which consists of 3 concepts related to the production of space, namely spatial practice, representational space, and spatial representation. The method of the research is qualitative with a descriptive method. In collecting the data, in-depth interviews were used with the informants who were closely related to the research being studied. The spatial contestation has indeed occurred in Tanjung Putat Beach and Lepar Beach, Belinyu District, Bangka Regency. However, the impact of mining activities has an impact on tourism in the vicinity, this is reinforced by protests against these mining activities.